Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-3/17 + 2/3 + 3/17 = (-3/17 + 3/17) + 2/3
= 0/17 + 2/3 (mà 0 chia bất kì số nào cũng = 0 )
= 0 + 2/3
= 2/3
:)))
b,\(\frac{2}{3}\)+\(\frac{1}{3}\).(\(\frac{-2}{3}\)+\(\frac{5}{6}\)):\(\frac{2}{3}\)
=\(\frac{2}{3}\)+\(\frac{1}{3}\).(\(\frac{-4}{6}\)+\(\frac{5}{6}\)):\(\frac{2}{3}\)
=\(\frac{2}{3}\)+\(\frac{1}{3}\).\(\frac{1}{6}\).\(\frac{3}{2}\)
=\(\frac{2}{3}\)+\(\frac{1}{18}\).\(\frac{3}{2}\)
=\(\frac{2}{3}\)+\(\frac{1}{6}\).\(\frac{1}{2}\)
=\(\frac{2}{3}\)+\(\frac{1}{12}\)
=\(\frac{8}{12}\)+\(\frac{1}{12}\)
=\(\frac{9}{12}\)=\(\frac{3}{4}\)
A = 2/7 + 11/7 -3/8 - 5/8 + 1/3 + 1/5 = 13/11 - 1 + 8/15
A = 2/11 + 8/15 = 118/125
B = - 3/17 + 3/17 + 2/13 = 2/13
C = - 3/8 - 5/8 + 12/15 = 1 - 12/15
C = - 1/5
\(\frac{9}{4}.\frac{7}{17}+2\frac{1}{4}.\frac{3}{17}-2,25.\frac{13}{17}\)
\(=\frac{9}{4}.\frac{7}{17}+\frac{9}{4}.\frac{3}{17}-\frac{9}{4}.\frac{13}{17}\)
\(=\frac{9}{4}.\left(\frac{7}{17}+\frac{3}{17}-\frac{13}{17}\right)\)
\(=\frac{9}{4}.\frac{-3}{17}\)
\(=\frac{-27}{68}\)
Nhớ k cho mình nhé
\(A=\frac{2}{7}+\left(-\frac{3}{8}\right)+\frac{11}{7}+\frac{1}{3}+\frac{1}{7}+\left(-\frac{5}{8}\right)\)
\(=\left(\frac{2}{7}+\frac{11}{7}+\frac{1}{7}\right)+\left(-\frac{3}{8}-\frac{5}{8}\right)+\frac{1}{3}\)
\(=2-1+\frac{1}{3}\)
\(=1+\frac{1}{3}\)
\(=\frac{4}{3}\)
\(B=-\frac{3}{17}+\left(\frac{2}{3}+\frac{3}{17}\right)\)
\(=-\frac{3}{17}+\frac{2}{3}+\frac{3}{17}\)
\(=\left(-\frac{3}{17}+\frac{3}{17}\right)+\frac{2}{3}\)
\(=0+\frac{2}{3}\)
\(=\frac{2}{3}\)
\(C=\frac{3}{8}+\frac{12}{25}+\frac{5}{-8}+\frac{2}{-5}+\frac{13}{25}\)
\(=\left(\frac{3}{8}-\frac{5}{8}\right)+\left(\frac{12}{25}+\frac{13}{25}\right)-\frac{2}{5}\)
\(=-\frac{1}{4}+1-\frac{2}{3}\)
\(=\frac{1}{12}\)
A -2/13+-11/26
=-4/26+-11/26
=-15/26
B 3/30+-1/5
=3/30+-6/30
=-3/30=-1/10
C -3/17+(2/3+3/17)
=( -3/17+3/17)+2/3
=2/3
D -5/7+3/4+-1/5+-2/7+1/4
=( -5/7+ -2/7)+(3/4+1/4)+ -1/5
=(-1)+1+ -1/5
=0+-1/5= -1/5
\(\frac{-3}{17}+\left(\frac{2}{3}+\frac{3}{17}\right)\)
\(=\frac{-3}{17}+\frac{2}{3}+\frac{3}{17}\)
\(=\left(\frac{-3}{17}+\frac{3}{17}\right)+\frac{2}{3}\)
\(=0+\frac{2}{3}\)
\(=\frac{2}{3}\)
-3/17 + (2/3 + 3/17)
= ( -3/17+3/17)+2/3
=0 + 2/3
= 2/3